(untitled) (Journal of Libya for geographical studies, 2022)
The research aims to reveal the characteristics of the age and sex composition of the population in the Gaza Strip, and to show their spatial variations between the administrative governorates based on the data of the three Palestinian censuses that were conducted during the years 1997, 2007, 2017, using a set of demographic methods such as the population pyramid, the median age of the population, and population aging, dependency rate, as well as the employment of graphic and cartographic forms. The results of the study indicated a demographic change in the characteristics of the age and gender structure of the population in the Gaza Strip.